Digital Forensics and Cyber Crime First International ICST Conference, ICDF2C 2009, Albany, NY, USA, September 30-October 2, 2009, Revised Selected Papers - Goel, Sanjay; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the First International ICST Conference, ICDF2C 2009, held September 30 - October 2, 2009, in Albany, NY, USA. Digital forensics and cyber crime is a multidisciplinary area that requires expertise in several areas including law, computer science, finance networking, data mining and criminal justice. The 16 papers present the whole gamut of multimedia and handheld device forensics, financial crimes, cyber crime investigations, forensics and law, cyber security and information warfare.
Full and Short Papers -- Digital Evidence Composition in Fraud Detection -- iForensics: Forensic Analysis of Instant Messaging on Smart Phones -- A Survey of Forensic Localization and Tracking Mechanisms in Short-Range and Cellular Networks -- SMIRK: SMS Management and Information Retrieval Kit -- Localization and Detection of Vector Logo Image Plagiarism -- Analysis of Free Download Manager for Forensic Artefacts -- On the Reliability of Cell Phone Camera Fingerprint Recognition -- Towards a New Data Mining-Based Approach for Anti-Money Laundering in an International Investment Bank -- Analysis of Evidence Using Formal Event Reconstruction -- Data Mining Instant Messaging Communications to Perform Author Identification for Cybercrime Investigations -- Digital Evidence Retrieval and Forensic Analysis on Gambling Machine -- Online Acquisition of Digital Forensic Evidence -- Criminal Defense Challenges in Computer Forensics -- Detecting and Preventing the Electronic Transmission of Illicit Images and Its Network Performance -- A Discretionary Access Control Method for Preventing Data Exfiltration (DE) via Removable Devices -- A Host-Based Approach to BotNet Investigation?.
Keywords: Computer science; Computer Communication Networks; Data mining; Computer vision; Biometrics; Computers -- Law and legislation; Computer Science; Data Mining and Knowledge Discovery; Computers and Society; Legal Aspects of Computing; Biometrics; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Communication Networks